Modelo de gestión del conocimiento en proyectos para la cooperativa de empleados del ministerio de educación pública. - Scafidi-Vargas, Antonieta (Instituto Tecnológico de Costa Rica, 2011)
Coopemep RL is a Savings and Credit Cooperative, ISO 9001:2008 certified company, which is regulated by the Superintendent of Financial Institutions (SUGEF), which in the law 14-09 of 17 requests the application control objectives of the Framework reference COBIT (Control Objectives for Information Technology and Related), where the goal PO10 Project Management is required. However, the General Management decided to implement enterprise-wide. For the past year and a half has a corporate project methodology, approved, communicated and applied to all projects in the institutional portfolio. All projects are aligned to the strategic business plan. Knowledge Management in an organization is the process by which there is a way to retrieve, index, store and distribute the knowledge contributed by each professional for any future activity. The knowledge generated in projects and their time of application has been characterized as being long and cumbersome. The lack of corporate memory is circumstantial when the organization is willingness on the part of people in search and reuse knowledge, but lacks an appropriate method for selection, storage, management and updating, in this way, stakeholders, the can not take it for finding non-existent, which corresponds to the case of Coopemep RL, seen in the documentation of existing projects. This research project will diagnose analyzed because the company is not handling skills and discover how knowledge management can assist in this process to strengthen and mature. Knowledge management is a fundamental principle that knowledge is the only resource that increases in value with use. Not degenerate but generates value. This is where the problem to solve is how to make a model that suits the environment Coopemep RL for knowledge management projects through the implementation of joint research, using the techniques of network analysis, systems analysis, SWOT analysis, analysis of organizational culture projects, interviews and surveys that collects information and triangles to ensure accuracy. It is thus concluded that the importance of organizational culture in projects for knowledge management projects thrive.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Área Académica de Gerencia de Proyectos, 2011.
Keywords: Comunicación; Conocimiento; Experiencia laboral; Activos; Capital; Impacto social